Dietary observations on the Asian softshell turtle (Amyda cartilaginea) from Sarawak, Malaysian Borneo - Jensen, Karen A.; Das, I. (Chelonian Research Foundation, 2008)
We examined the diet of Amyda cartilagi-nea from 2 localities in Sarawak: Loagan BunutNational Park and Balai Ringin. The most commonlyfound items in stomach contents, when using percent-age frequency of occurrence, were plant material(77%) and unknown vertebrate parts (55%). Fecalanalysis indicated similar results: plant material(100%), unknown vertebrate parts (84%), ﬁsh (69%),and unknown arthropods (62%). Results indicate thatA. cartilaginea is an opportunistic omnivore.